2022
DOI: 10.1126/scirobotics.abg4055
|View full text |Cite
|
Sign up to set email alerts
|

BirdBot achieves energy-efficient gait with minimal control using avian-inspired leg clutching

Abstract: Designers of legged robots are challenged with creating mechanisms that allow energy-efficient locomotion with robust and minimalistic control. Sources of high energy costs in legged robots include the rapid loading and high forces required to support the robot’s mass during stance and the rapid cycling of the leg’s state between stance and swing phases. Here, we demonstrate an avian-inspired robot leg design, BirdBot, that challenges the reliance on rapid feedback control for joint coordination and replaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 121 publications
0
23
0
Order By: Relevance
“…The CoT values of the GAS + SOL, SOL and GAS configurations were 55 %, 50 % and 119 % of the approximated CoT of a natural walker with the same weight as these configurations (calculation method in [15]). Many factors could influence the CoT, a freely walking robot on natural terrain and with trunk control would probably consume more power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CoT values of the GAS + SOL, SOL and GAS configurations were 55 %, 50 % and 119 % of the approximated CoT of a natural walker with the same weight as these configurations (calculation method in [15]). Many factors could influence the CoT, a freely walking robot on natural terrain and with trunk control would probably consume more power.…”
Section: Discussionmentioning
confidence: 99%
“…A simulation study showed that combining mono-and bi-articular foot prosthesis actuation reduces peak power requirements [14]. BirdBot's springtendon network improved cost of transport, and enabled robust engagement and disengagement of the leg's parallel elasticity [15]. So far, the exact role and function of plantarflexor spring-tendons as part of the swing leg catapult during walking has not been studied in robots.…”
Section: Introductionmentioning
confidence: 99%
“…In a lab experiment with simulated moon gravity, PEAs reduced the energy required for a jump by a factor of two on this robot [10]. Another, more recent example of using PEA is BirdBot [11], which has a parallel elastic spring clutching mechanism, spanning multiple joints. The avian-inspired leg design shows self-stable and robust bipedal locomotion while requiring 10 % of the knee-flexing torque compared to a nonclutching parallel spring setup.…”
Section: A Robots With Elastic Actuatorsmentioning
confidence: 99%
“…Building upon intuitive design, a common approach starts with mimicking nature's counterparts [13]. Atrias [4] and BirdBot [11] for instance are inspired by ostriches and the emu. The problem with bio-inspired design is the high amount of variables that need to be taken into account to fully model the targeted animal accurately.…”
Section: A Robots With Elastic Actuatorsmentioning
confidence: 99%
“…Instead of regulating the damper's force by adjusting the orifice size, we propose damping control by adjustment of the damper tendon slack. Tendon slack has been observed in biology, with tendon stretch up to 2% of the nominal tendon length before starting to produce considerable force [39][40][41] . This is known as the 'toe region' in the tendon's stress-strain diagram.…”
Section: Slack Damper Mechanismmentioning
confidence: 99%